(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article examines the circumstances that must be clarified during the investigation.Criminal cases related to the illegal circulation of Drugs, Psychotropic Substances and their analogues are important for strengthening the evidence base. It is noted that their timely identification and proof will contribute to a complete, comprehensive and objective examination.